The Effect of Compliance with Islamic Accounting Standards on the Profitability of Islamic Banks in Indonesia - Mardi (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to analyze the effect of Compliance with Islamic Accounting Standards (CIAS) on the profitability of Islamic banks in Indonesia, proxied by Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). Compliance with Islamic accounting standards is considered an important indicator in reflecting the transparency, accountability, and quality of financial reporting in Islamic financial institutions. This study employed a quantitative approach using an explanatory research method involving 40 Islamic banks registered with the Financial Services Authority during the 2020–2024 period, selected through purposive sampling techniques. Secondary data were obtained from annual financial reports and analyzed using descriptive analysis, classical assumption tests, multiple linear regression, hypothesis testing, and coefficient of determination analysis. The results indicate that Compliance with Islamic Accounting Standards has a positive and significant effect on all profitability indicators, namely ROA (0.001), ROE (0.026), and NPM (0.001). These findings suggest that higher compliance with Islamic accounting standards leads to higher profitability among Islamic banks. This study contributes to the development of Islamic accounting knowledge and serves as a reference for Islamic bank management and regulators in improving compliance quality to support sustainable financial performance.